Value of voluntary carbon markets in energy systems decarbonization - John Bistline; Anahi Molar-Cruz; Geoffrey Blanford; Adam Diamant (npj Climate Action)
Abstract Although companies are pledging emissions reductions, technical and economic challenges persist, particularly for factors beyond direct corporate control. Given these uncertainties, voluntary carbon markets could play key roles in achieving affordable and reliable decarbonization. This analysis employs a detailed energy systems model to quantify how the value of carbon markets varies across different regional, technological, and policy contexts. Results suggest that carbon markets can reduce electricity decarbonization costs by 50% in many regions, particularly by substituting costly direct mitigation strategies involving uncertain emerging technologies. This value increases under conditions with high technological costs, limited portfolios, and deeper economy-wide decarbonization, highlighting the potential of voluntary carbon markets as hedges against technological and policy uncertainties. Additionally, regional cost differences are significant, ranging from −66% to +49% relative to national averages, underscoring that flexible approaches to emissions reductions across sectors, regions, and technologies enhance affordability and feasibility of net-zero targets.